PENGARUH HARGA, KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN PADA PT BENTENG INDO BANGUNAN - Sandy Sandy; Sunargo Sunargo (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2023)
The potential for the city of Batam to develop is still quite large so that many investors invest by constructing projects in the form of housing, buildings that are used as shopping centers, warehouses, hotels and others. PT Benteng Indo Building is known as a company engaged in the sale of building materials in the city of Batam. The company PT Benteng Indo Bangunan always emphasizes that customer satisfaction is the company's priority but the company does not experience a large increase in customers. This is because the price, product quality and service quality at the company are not optimal. This study aims to determine the effect of price, product quality, service quality on customer satisfaction. The method used in this research is quantitative. The results of this study have the effect of price, product quality, service quality on customer satisfaction. By 87.2% the influence of price, product quality, service quality on customer satisfaction and 22.8% influenced by other variables.